INVESTASI DALAM PERSPEKTIF EKONOMI SYARIAH - Susana, Lina Marlina; Safitri, Nurlita (FASTABIQ: JURNAL STUDI ISLAM, 2023)
The lack of public understanding of investment has resulted in many investors investing in industries thar produce and sell illegal products or illicit goods. There are also cases of people falling into fraudulent or (illegal) investments’his research is intended to provide insight into the perspective that Investment Outlook can simply be referred to as a way to develop income and can help us avoid inflation, with sharia investments, namely: musyarakah or shirkah (partnership) contracts, mudarabah or qirad contracts, leasing-leasing (ijarah), kafalah contract (collateral) and wakalah contract (representing). As well as giving the view that there are several investments that contradict sharia principles, examples of prohibited investments are: investments that contain usury (additional), gharar (uncertain), maysir (gambling), vanity, and Bay’i ma’dum. This research is a qualitative approach using content analysis in literature study. That is doing descriptive analytical on exiting sources both from book manuscripts and various journal articles obtained. Results, here’s an effective way to avoid illegal investment, 1). Be careful if you receive a very attractive prize offer, 2) make it a habit to check licensing/approval documents for investment institutions or companies, 3) examine the forms and methods of these Comines in marketing their investment products, 4) may not hand over funds before making and signing a formal and detailed agreement, and 5) immediately report any illegal investment. Keywords; Economic; Investment; Sharia